Unmet weight loss targets in real-world clinical practice: weight management and perceptions in China - Lin, Ziwei; Si, Si; Liu, Jia; Zhu, Hao; Xu, Jiawei; Artime, Esther; Khare, Swarna; Higgins, Victoria; Leith, Andrea; Qu, Shen (Frontiers in Endocrinology, 2024)
The rising prevalence of obesity and overweight in China presents a major public health challenge. However, public awareness of weight management is low and weight management in clinical practice is suboptimal. In this article, we present an analysis of data from the Adelphi Real World Obesity Disease Specific Programme TM with the objective of describing current weight management and perceptions in China. Our findings suggested that obesity diagnosis may be delayed and that physicians focused on treating obesity-related complications rather than prioritizing the management of obesity. While most physicians and people with obesity (PwO) recognized the importance of normal weight, few PwO achieved their weight loss targets, and neither physicians nor PwO were satisfied with the outcomes of the current weight loss attempts. We believe that these results will be of interest to the readers of Frontiers in Endocrinology as they provide valuable insights into weight loss management in China, suggesting an unmet need for improved weight loss awareness and early and effective weight loss interventions.